A mathematical question for no real reason!

  • Hey Guest, We're having our annual Winter Moot and we'd love you to come. PLEASE LOOK HERE to secure your place and get more information.
    For forum threads CLICK HERE

Stew

Bushcrafter through and through
Nov 29, 2003
6,769
1,521
Aylesbury
stewartjlight-knives.com
Ok, so bear with me on the description on this as it may not make sense.


This number sequence:







The next value = the previous value + the previous difference to add multiplied by three.


Can anyone write a formula on how to calculate, for example, the 15th value without having to calculate the previous 14? I have been pondering and my meager brain can't do it.


There is no real end goal on this - it's just curiosity.


It may not be possible, of course..... :D
 
If place number = x and value = y then:

Hang on... made a cock up in the formula...

The 15th value (x=15) is 1,594,323
 
Last edited:
If place number = x and value = y then:

y=(x-1)+(3^(x-1))

So, if x=6 (i.e. place number 6), y=122 (41+81)

The 15th value (x=15) is 1,594,323


Not that I can see using excel.

I've had it suggested that the first difference should be 3 not 1 but if the first difference is 1, second 3 (as above) then the 15th value = 2391485. If the first difference is 3, second is 9 then the 15th value = 7174453. That's using two lines of excel formulas.

Forgive my ignorance - what's the up arrow signify after the 3 in your formula?
 
Last edited:
Sorry, made a complete hash in the spreadsheet I was using to calculate the value.

15th value, I am now pretty sure, is now 2,391,485 but it's summing powers of 3 (the up arrow symbol means "to the power" so 3^3 is the same as 3*3*3 or 3 cubed etc.)
 
Well you have the right answer - what's your formula? :D

I'd initially calculated that by using a spreadsheet and adding numbers as I went along, much like you probably did. However, I wasn't satisfied that a formula couldn't be found so after a bit of searching around, I wrote this:

y=2+(3*(1-(3^(x-2)))/-2)

So, for example, if x=4, then y=2+(3*(1-(3^2)))/-2; y=2+(3*(1-9))/-2; y=2+(-24/-2); y=2+12; y=14

Simple :D
 

BCUK Shop

We have a a number of knives, T-Shirts and other items for sale.

SHOP HERE